Intraspecific non-sexual interactions of Grammostola schulzei (Araneae: Theraphosidae) under laboratory conditions - Nelson E Ferretti; Fernando Pérez-Miles (Revista de Biología Tropical, 2011)
Intraspecific interactions of araneomorph spiders have received considerable attention, but there are few detailed studies on intraspecific interactions of mygalomorph spiders. Moreover, a thorough understanding of theraphosid biology and ecology is necessary from a conservation standpoint because natural populations may be threatened by habitat disturbances and captures for pet commerce. We described the behavior of conspecific individuals of Grammostola schulzei during non-sexual interactions, under laboratory conditions. Pairs of individuals involving adult males, adult females and juveniles were confronted and observed in resident and intruder conditions, totalizing 115 trials. When confronted two adult females, they retreated or grappled, and performed gaping display with bite attempts, usually resulted in severe injury of the intruder spiders. When confronted females with large juveniles, we frequently observed cannibalism on juveniles. Juveniles exposed to females or to other juveniles retreated or made leg tapping with forelegs and palpal drumming, which are common displays of courting adult males. Adult males courted and clasped some juveniles, but juveniles avoided or reject clasping. The behaviors observed during intraspecific interactions could play an important role determining spatial distribution and could lead to behavioral adaptations of territoriality. Rev. Biol. Trop. 59 (3): 1173-1182. Epub 2011 September 01. Hay pocos estudios detallados sobre las interacciones intraespecíficas de arañas migalomorfas. Por lo tanto, se describe el comportamiento de individuos conspecíficos de Grammostola schulzei durante interacciones nosexuales en condiciones de laboratorio. Se confrontaron y observaron pares de individuos involucrando machos adultos, hembras adultas y juveniles en condiciones de locatarios y visitantes, totalizando 115 encuentros. Cuando dos hembras adultas se enfrentaron, retrocedieron o lucharon adoptando elevaciones anteriores e intentos de mordeduras que usualmente resultaron en arañas visitantes heridas. Cuando se enfrentaron hembras con juveniles, frecuentemente se observó canibalismo sobre los juveniles. Los juveniles expuestos a otros juveniles o hembras retrocedieron o realizaron golpes con patas delanteras y tamborileos de palpos, los cuales constituyen unidades de comportamiento comunes durante el cortejo de los machos. Los machos adultos cortejaron y trabaron a algunos juveniles, mientras que los juveniles los evitaron o rechazaron el enganche. Los comportamientos observados durante las interacciones intraespecíficas podrían jugar un papel importante en la distribución espacial y podrían generar adaptaciones al territorialismo.